Preliminary Exploration of Caregiver Stress Responses after a Child's Premature Delivery. Issue 3 (3rd July 2021) - Lavine, Debbie; Jewell, Vanessa D.; Greiner, Bobbi
ABSTRACT: Caregivers frequently find the premature birth of a child as a crisis. This pilot study explored the perceived types of stress experienced by parents of premature infants and the impact on caregiving. Caregivers completed the Impact of Events Scale-Revised (IES-R; n = 4) and participated in a focus group (n = 3) or interview (n = 1). Caregivers' total scores on the IES-R ranged from 2 to 42. Themes included: emotions experienced at birth through the present, occupational loss, and the role of occupational therapy in the home. Although preliminary, findings indicated caregivers experienced high levels of stress that may impact co-occupations with premature infants.